MicroRNA-139-5p Suppresses Cell Malignant Behaviors in Breast Cancer through Targeting MEX3A - Jian Chu (Hindawi Limited, 2021)
Objective. The study was designed to evaluate the underlying mechanism of microRNA-139-5p in breast cancer (BC). Methods. Expression statuses of microRNA-139-5p and MEX3A were measured by qRT-PCR and western blotting. The anticancer effect of microRNA-139-5p in vitro was tested by a set of assays. Interaction between microRNA-139-5p and MEX3A was validated by dual-luciferase detection. Results. MicroRNA-139-5p expression in BC cells was obviously low, while MEX3A was significantly overexpressed. MicroRNA-139-5p restrained proliferative, invasive, and migratory abilities of BC cells and increased apoptosis level of BC cells, while MEX3A exerted a promoting effect on BC cell growth. Dual-luciferase reporter detection confirmed that microRNA-139-5p bound to MEX3A 3′-UTR. Conclusions. MicroRNA-139-5p inhibited the development of BC by targeting MEX3A. MicroRNA-139-5p/MEX3A may be a target for BC therapy.